Moloduwo: Tradisi "undangan" pada Muslim Gorontalo dalam Perspektif Komunikasi - Maskun Otoluwa, Hidayatullah; Iloha, Abdurahman (Farabi, 2023)
Abstract: This research aims to examine the implementation of moloduwo in Gorontalo society. Knowing how the stages of moloduwo implementation and revealing the meaning of existing symbols. The research method used is descriptive qualitative method with communication ethnography approach. This research was conducted in all customary areas in Gorontalo Province. This research covers field research and archival/library research. Data collection was done through observation, interview, and document analysis. The results of this study show that the implementation of moloduwo carried out both in joyful events (liya-liyango) and in mourning events (bayabulilo) has a clear meaning, namely each stage of its implementation has a meaning conveyed in the form of verbal and non-verbal message symbols. Keywords: Moloduwo ; symbol; liya-liyango ; bayabulilo